Bystanders in "sketchy" sexual situations: Their constructions of the "girl, " the "guy, " and themselves. (August 2019) - Lamb, Sharon; Attwell, Leah
In this paper we explore through discourse analysis the written personal narratives (vignettes) of "sketchy" sexual situations that students found themselves in as bystanders. We asked for these vignettes in a larger study examining the relationships between moral judgment/reasoning and intervening or not in situations of potential sexual assault. Through a Foulcauldian Discourse Analysis (FDA), we explore in these narratives discursive constructions, positioning of potential victims, potential perpetrators, and bystanders of sexual assault, as well as the action orientations these discourses suggest, and the implications for rape prevention programs.